Analisis Pusat Pertumbuhan di Kabupaten Karangasem - Andriyani, Ni Nyoman Sri; Utama, I Made Suyana (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 4, No. 4, April 2015 (pp. 220 - 348), 2015)
Karangasem regency needs special attention of the government to solve the economic problems that it faced . Karangasem regency in this research ranked second lowest in terms of economic growth and to obtain a high number for the percentage of poor people in the province of Bali after Jembrana . Besides that, Karangasem is also fairly low which is reflected in the GDP per capita of Karangasem regency over the past five years occupies the lowest position in the province of Bali . This study aims to determine the classification of economic growth pattern and sector base of each district in Karangasem and to know how much connection / attraction between districts which are defined as the center of economic growth in Karangasem with other sub-districts in Karangasem regency . The analytical tool used is Klassen Typology , Location Quotient ( LQ ) , and analysis of Gravity Model . Based on the analysis results obtained from the three analysis tools are used , that Kecamatan Manggis and Kecamatan Karangasem  is appropriately set as the center of growth because it has the criteria developed and rapidly growing area ( Type I ) , has a relationship with the surrounding sub-districts , and has a sector potentially export base.
Keywords: growth pole, klassen typology, basic sector, gravity models